Pengaruh Model Pembelajaran Cooperative Script Terhadap Hasil Belajar PAK Siswa Kelas IX SMP Negeri 3 Sipoholon Tahun Pembelajaran 2019/2020 - Irwan Putra Zai (Areopagus : Jurnal Pendidikan Dan Teologi Kristen, 2020)
This study aims to determine whether there is an influence of Cooperative Script learning models on PAK learning outcomes of grade IX students of SMP Negeri 3 Sipoholon. Correlational research of Descriptive and Inferential Statistics techniques.               The population of all class IX Christians is 108 people. The sample uses Purposive Sampling technique that is class IX-A students totaling 35 people. The research instrument was a closed questionnaire variable X and test variable Y. The results of the analysis of the value of rxy = 0.553 r table = 0.334 and tcount = 3.813 t table = 2.042 showed a relationship and obtained the significance of a simple regression equation, i.e.                This study concludes that there is a positive and significant effect of Cooperative Script learning models on the learning outcomes of PAK students of grade IX SMP Negeri 3 Sipoholon by 30.58%.                                              Keywords: Cooperative Script Learning Model, Christian Religious Education Learning Outcomes.